(untitled) (Revista "Boletín el Conuco", 2024)
This article comes from a research project developed in Valladolid, Yucatán state, Mexico, applied to 8 nano-companies that are dedicated to growing vegetables in backyards where the objective was to determine the optimal distribution channels used for marketing. of the vegetables from their homes to the final consumer, for this a descriptive research was used, because the characteristics of the distribution channels of the vegetables were known and the situation of the company was diagnosed using two questionnaires: the first of them applied to the 52 microenterprises to know their degree of commercialization of vegetables coming from families (nanoenterprises) and the second to 69 people to know the desired purchasing channels. The results indicated that the main means of purchasing vegetables, ordered from highest to lowest proportion, are: local market, fruit shops and supermarket, also to a lesser extent directly from the producer, street vendor, retailers in the neighborhoods and convenience stores located in the neighborhoods. It is concluded that 50% of the nanocompanies move their products directly to the customer while the other 50% sell it through an intermediary, so the nanocompanies dedicated to the cultivation of backyard vegetables are not using the optimal distribution channels.